PENGGUNAAN KLAUSULA BAKU DALAM PERJANJIAN E-COMMERCE DI TINJAU DARI PERSPEKTIF PERLINDUNGAN KONSUMEN - Fadel Edo Romires (Sekolah Tinggi Pariwisata Mataram, 2022)
Abstract The rapid and advanced achievement of internet technology makes it easier to access any information needed, including product information. The existence of this convenience makes it a very important potential to be able to influence trading patterns, whether done online. The ability of these computers to be interconnected with one another opens up opportunities for the emergence of a new marketing method for commercial products, both in the form of goods and services. This method of marketing or buying and selling via the internet is known as electronic commerce (e-commerce). Currently, there is no definite definition of e-commerce that has been standardized and mutually agreed upon, but in the general sense accepted by the community, e-commerce is trade carried out via the internet. The existence of standard clauses as a medium to facilitate buying and selling transactions between producers and consumers turns out to be misused by producers by providing conditions that are very detrimental to consumers, including in banking credit agreements, insurance agreements, goods custody agreements, and buying and selling agreements through e-commerce. . One of the standard clauses reads